2021
DOI: 10.1590/1809-4430-eng.agric.v41n1p19-24/2021
|View full text |Cite
|
Sign up to set email alerts
|

Ingestive Behavior of Santa Inês Sheep Under Thermoneutrality and Thermal Stress Upon Consumption of Saline Water

Abstract: The consumption of saline water in semiarid regions is a recurrent situation that can affect the ingestive behavior of small ruminants. This study evaluated the ingestive behavior of Santa Inês sheep maintained in a climatic chamber under two air temperatures-25 °C within the thermal comfort zone (TCZ) and 32 °C above the TCZ-and consuming water with three levels of salinity-2.0, 4.0, and 8.0 dS m-1. The experimental design was completely randomized in 2 × 3 factorial schemes, comprising two air temperatures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…Saline water also affected the other behaviors of goats, such as eating, drinking, and standing time (Table 3; p<0.05). However, Furtado et al (2021) found that saline water concentrations ranging from 0.2 to 0.8% did not affect consumption behaviors and obtained results different from those found in the present study. The diluted seawater groups spent more time eating and drinking than the goats drinking freshwater, and the frequency of eating events was lower than that in control group, especially between the A0 and control groups.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Saline water also affected the other behaviors of goats, such as eating, drinking, and standing time (Table 3; p<0.05). However, Furtado et al (2021) found that saline water concentrations ranging from 0.2 to 0.8% did not affect consumption behaviors and obtained results different from those found in the present study. The diluted seawater groups spent more time eating and drinking than the goats drinking freshwater, and the frequency of eating events was lower than that in control group, especially between the A0 and control groups.…”
Section: Discussioncontrasting
confidence: 99%
“…These behaviors encompass individual activities of animals and are influenced by environmental factors, such as air temperature, humidity or water quality (Custodio et al 2017). Animal performance may depend on behavior activities, diets, breeding as mentioned by Costa et al (2019) and Furtado et al (2021). Although in this study the behavior data were collected on the day 55 of the experiment, the results revealed that the goats were affected by either the saline water or tropical climate.…”
Section: Discussionmentioning
confidence: 79%
“…The DM digestibility was reduced for animals that were exposed to a higher temperature. This fact can be attributed to the intake of saline water because the level of salinity of the water can interfere with the intake and digestibility of nutrients (Furtado et al, 2021). Salt intake can alter the fermentation pattern in the rumen, affecting the acid-base balance.…”
Section: Discussionmentioning
confidence: 99%